2022
DOI: 10.1128/spectrum.02583-21
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-Binding Oligomerization Domain 1 (NOD1) Positively Regulates Neuroinflammation during Japanese Encephalitis Virus Infection

Abstract: Neuroinflammation is the main pathological manifestation of Japanese encephalitis (JE) and the most important factor leading to morbidity and death in humans and animals infected by JEV. An in-depth understanding of the basic mechanisms of neuroinflammation will contribute to research on JE treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Another study indicated that, loss of NOD1 accelerated obesity in mice fed a HFD, accompanied by increased levels of free thyroidal T4, reduced expression of uncoupling protein 1 (UCP1) in brown adipose tissues, and enhanced infiltration of inflammatory cells in white adipose tissues and liver tissues, suggesting a protective role of NOD1 against inflammation and obesity [ 68 ]. Infection with Japanese encephalitis virus (JEV) greatly elevated the transcriptional and protein expression of NOD1 in mice, and knockout of NOD1 enhanced resistance to JEV infection by inhibiting the neuroinflammatory response and multiple downstream signaling pathways [ 69 ]. Knockout of NOD1 also significantly decreased the number of isolated lymphoid follicles in the distal ileum and colon of mice and greatly increased the total number of bacteria in the ileum to affect intestinal homeostasis [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study indicated that, loss of NOD1 accelerated obesity in mice fed a HFD, accompanied by increased levels of free thyroidal T4, reduced expression of uncoupling protein 1 (UCP1) in brown adipose tissues, and enhanced infiltration of inflammatory cells in white adipose tissues and liver tissues, suggesting a protective role of NOD1 against inflammation and obesity [ 68 ]. Infection with Japanese encephalitis virus (JEV) greatly elevated the transcriptional and protein expression of NOD1 in mice, and knockout of NOD1 enhanced resistance to JEV infection by inhibiting the neuroinflammatory response and multiple downstream signaling pathways [ 69 ]. Knockout of NOD1 also significantly decreased the number of isolated lymphoid follicles in the distal ileum and colon of mice and greatly increased the total number of bacteria in the ileum to affect intestinal homeostasis [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Later, on a murine model of JEV infection, it is demonstrated that production of reactive oxygen species and potassium efflux are critical for the maturation of NLRP3 inflammasome, activation of caspase-1, and subsequent secretion of IL-1β and IL-18 [341]. In addition, JEV could upregulate the expression of NOD1, leading to an enhanced neuroinflammatory response, and NOD1 activation is shown to play the role in the inflammatory response triggered by JEV infection [342]. Interestingly, JEV is found to develop the protection mechanism against host microRNAs [343] (Table 6).…”
Section: Flaviviridae Nonstructural Proteins' Interference With Nlr S...mentioning
confidence: 99%
“…The mechanisms of JE, including neuroinflammation ( 22 ), neuroinvasion ( 23 ), neuroimmunity, neurocytes damage or death ( 24 ), and mitophagy ( 25 ), are complicated and have not been elucidated; nonetheless, some progress has been made in recent years. The acute flaccid paralysis associated with JEV infection is caused by extensive brain lesions ( 26 ) and degeneration and death of motor neurons in the anterior horn of the spinal cord ( 27 ).…”
Section: Introductionmentioning
confidence: 99%